Exploring the Complementary Role of Traditional Chinese Medicine in Enhancing Percutaneous Coronary Intervention Outcomes: Mechanisms, Benefits, and Future Research Directions - Zheng S; Guo J; Wang Q (Therapeutics and Clinical Risk Management)
Sidao Zheng,1 Jun Guo,2 Qi Wang2 1Department of Cardiology, Beijing Hospital of Integrated Traditional Chinese and Western Medicine, Beijing, 100039, People’s Republic of China; 2Senior Department of Cardiology, The Sixth Medical Center of PLA General Hospital, Beijing, People’s Republic of ChinaCorrespondence: Sidao Zheng, Department of Cardiology, Beijing Hospital of Integrated Traditional Chinese and Western Medicine, Beijing, 100039, People’s Republic of China, Email zhengsidao@gmail.comBackground: Percutaneous coronary intervention (PCI) is a cornerstone treatment for coronary artery disease (CAD), yet opportunities remain to improve clinical outcomes, symptom management, and long-term prognosis. Traditional Chinese Medicine (TCM), with its multi-target and multi-pathway mechanisms, offers a promising complementary approach to enhance PCI efficacy.Methods: A systematic search was conducted in PubMed and Web of Science using the terms: (“Percutaneous Coronary Intervention” AND “Traditional Chinese Medicine”) and (“Percutaneous Coronary Intervention” AND “Chinese Herbal Drugs”). Randomized controlled trials (RCTs) with ≥ 100 participants were included to evaluate TCM’s clinical efficacy in PCI. Pharmacological studies were also reviewed to explore underlying mechanisms.Results: A review of 20 RCTs showed that TCM plays multiple roles in CAD treatment during PCI. Specific interventions such as Danhong Injection, Tongxinluo Capsule, and Shenzhu Guanxin Granule were found to alleviate angina symptoms, restore cardiac function, reduce cardiac biomarkers, prevent no-reflow/slow-flow phenomena, inhibit in-stent restenosis, and improve prognosis while reducing complications. Mechanistically, TCM exerts its effects through antiplatelet action, anti-inflammation, inhibition of smooth muscle proliferation, vasodilation, microcirculation improvement, and endothelial protection.Conclusion: This systematic review highlights the complementary benefits of TCM in PCI for CAD patients. Effective interventions such as Danhong Injection and Tongxinluo Capsule contribute to symptom relief, cardiac function restoration, restenosis inhibition, and prognosis improvement. These benefits are linked to TCM’s multi-target mechanisms, including anti-inflammatory and antiplatelet effects. Future high-quality studies are needed to further validate these findings and refine clinical applications.Keywords: coronary artery disease, traditional Chinese medicine, percutaneous coronary intervention, randomized controlled trials, clinical efficacy, mechanisms of action